2022
DOI: 10.21037/jtd-22-763
|View full text |Cite
|
Sign up to set email alerts
|

Study on the predictive ability of emergency CHADS2 score and CHA2DS2-VASc score for coronary artery disease and prognosis in patients with acute ST-segment elevation myocardial infarction

Abstract: Background: Acute ST-segment elevation myocardial infarction (STEMI) has a high morbidity and mortality rate. The congestive heart failure, hypertension, age, diabetes, previous stroke/transient ischemic attack (2 points) (CHADS 2 ) and CHADS 2 score with 2 points assigned for age >75 years-vascular disease (CHA 2 DS 2 -VASc) scores are widely used for risk stratification management of non-valvular atrial fibrillation stroke and have high prognostic value in cardiovascular disease. This study aims to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…The results of this study highlighted the prognostic value of the CHADS2, CHA2DS2-VASc, and R2-CHADS2 scores in patients with NSTEMI. Although previous research has demonstrated the utility of these scores in patients with CAD and STEMI, 13,14 this study is the first to specifically focus on patients with NSTEMI. Notably, patients with NSTEMI often exhibit a poorer long-term prognosis than those with STEMI and have lower rates of optimal drug therapy implementation after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study highlighted the prognostic value of the CHADS2, CHA2DS2-VASc, and R2-CHADS2 scores in patients with NSTEMI. Although previous research has demonstrated the utility of these scores in patients with CAD and STEMI, 13,14 this study is the first to specifically focus on patients with NSTEMI. Notably, patients with NSTEMI often exhibit a poorer long-term prognosis than those with STEMI and have lower rates of optimal drug therapy implementation after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat banyak macam risk score stroke, misalnya CHADS2 Risk Score, CHA2DS2-VASc Risk Score, ATRIA Risk Score, dan Framingham Risk Score. CHADS2 Risk Score adalah metode skoring risiko stroke yang paling sederhana karena hanya mempertimbangkan beberapa faktor, yaitu riwayat penyakit gagal jantung, hipertensi, umur, dan riwayat penyakit stroke [4]. CHA2DS2-VASc Risk Score merupakan pengembangan dari CHADS2 Risk Score, memiliki faktor risiko yang sama, namun dengan tambahan riwayat penyakit pembuluh darah dan jenis kelamin [4].…”
Section: Pendahuluanunclassified
“…CHADS2 Risk Score adalah metode skoring risiko stroke yang paling sederhana karena hanya mempertimbangkan beberapa faktor, yaitu riwayat penyakit gagal jantung, hipertensi, umur, dan riwayat penyakit stroke [4]. CHA2DS2-VASc Risk Score merupakan pengembangan dari CHADS2 Risk Score, memiliki faktor risiko yang sama, namun dengan tambahan riwayat penyakit pembuluh darah dan jenis kelamin [4]. ATRIA Risk Score memiliki factor risiko yang sama dengan CHA2DS2-VASc Risk Score, namun dengan tambahan faktor kelainan ginjal yang diukur dengan estimated glomerular filtration rate (eGFR) yaitu laju penyaringan darah dan end-stage renal disease (ESRD) yaitu gagal ginjal kronis [5].…”
Section: Pendahuluanunclassified
“…In patients with established coronary artery disease, the CHA 2 DS 2 -VAS C score has been demonstrated to predict the development of atrial fibrillation [26][27][28], ischemic severity [29,30], and stroke [27,[31][32][33][34]. CHA 2 DS 2 -VAS C also been shown to estimate the prognosis and predict the mortality of these patients [34][35][36][37][38][39][40][41]. However, almost all studies were done on patients with acute coronary syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Although CHADS 2 and CHA 2 DS 2 -VAS C scores were initially developed to predict stroke in patients with atrial fibrillation [1-3], they were later used to predict multiple cardiovascular outcomes in different categories of patients [7,8,[11][12][13][14][18][19][20][21]23,[25][26][27][29][30][31][34][35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%